Intravenous immunoglobulin as short- and long-term therapy of multifocal motor neuropathy: a retrospective study of response to IVIg and of its predictive criteria in 40 patients. Issue 1 (13th December 2007) - Léger, J-M; Viala, K; Cancalon, F; Maisonobe, T; Gruwez, B; Waegemans, T; Bouche, P
Abstract : Objective: To document short-term and long-term responses to a single type of intravenous immunoglobulin (IVIg) in a large cohort of patients with multifocal motor neuropathy (MMN). Methods: A retrospective study was conducted in 40 patients with MMN included on ENMC Workshop criteria, and treated with periodic IVIg infusions between 1995 and 2003. The short-term response was defined as improvement of at least 1 point on the MRC score in at least two affected muscles at 6 months. The population comprised 22 treatment-naïve patients (who had never received IVIg before inclusion), and 18 previously treated patients. For the long-term evaluation (>6 months), the patients were classified into three groups according to the dependency or not on periodic IVIg. In addition, changes in conduction block (CB) and predictive criteria for response to IVIg were explored. Results: The MRC score significantly improved (p<0.0001) in 14 (70%; 95% CI 0.46 to 0.88) of the 20 treatment-naïve patients (missing data for 2 patients). None of the predictive criteria studied were found to be significant. At the end of follow-up (mean of 2.2±2.0 years), only 8 of the 40 patients (22%) had significant remission, whereas 25 patients (68%) were dependent on periodic IVIg infusions. The number of CBs decreased or remained unchanged in 12 treatment-naïve patients and increased in 2 such patients. Conclusions: This study confirmed a significantly high short-term response to IVIg of patients with MMN, but showed contrasted results in long-term follow-up. No predictive factors for response to IVIg were found.